2023
DOI: 10.2147/dddt.s425654
|View full text |Cite
|
Sign up to set email alerts
|

Escitalopram Personalized Dosing: A Population Pharmacokinetics Repository Method

Xin Liu,
Gehang Ju,
Wenyu Yang
et al.

Abstract: Escitalopram (SCIT) represents a first-line antidepressant and antianxiety medication. Pharmacokinetic studies of SCIT have demonstrated considerable interindividual variability, emphasizing the need for personalized dosing. Accordingly, we aimed to create a repository of parametric population pharmacokinetic (PPK) models of SCIT to facilitate model-informed precision dosing. In November 2022, we searched PubMed, Embase, and Web of Science for published PPK models and identified eight models. All the structura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…The most influential covariate was body size, such as body weight and BSA. Three [ 15 , 19 , 34 ] studies (23.1%) found body weight closely related to CL, and five studies [ 12 , 23 , 28 , 33 , 34 ] (38.5%) indicated its impact on V d . Yang et al [ 27 ] and Niu et al [ 25 ] identified BSA as a crucial covariate that affects both CL and V d .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most influential covariate was body size, such as body weight and BSA. Three [ 15 , 19 , 34 ] studies (23.1%) found body weight closely related to CL, and five studies [ 12 , 23 , 28 , 33 , 34 ] (38.5%) indicated its impact on V d . Yang et al [ 27 ] and Niu et al [ 25 ] identified BSA as a crucial covariate that affects both CL and V d .…”
Section: Resultsmentioning
confidence: 99%
“…Literature evaluations were implemented to diligently identify and resolve any anomalies or inconsistencies pertinent to the construction of the model library [ 15 ]. The quality of the popPK study was evaluated based on a checklist with 33 items adapted from the guidelines (see Supplementary Materials ) [ 16 , 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…The assessment of the quality of the included studies was performed by utilizing a 33-item checklist, consisting of 5 categories, as presented in Table S1, according to previous popPK systematic review quality assessment method. [19][20][21][22] This checklist was designed to assess the essential components required for the reporting of clinical pharmacokinetic (PK) studies. For each item, one point was assigned if the involved literature met the criteria, whereas incomplete data were assigned 0.5 points.…”
Section: Literature Quality Assessmentmentioning
confidence: 99%
“…Monte-Carlo simulations can predict the effect of different factors on drug exposure and estimate the probabilities of achieving the desired treatment outcome. Previous studies have successfully applied this approach to other drugs and created model repositories, [19][20][21][22] which enable the use of model averaging/selection methods and enhance the prediction performance of MIPD. 23,24 There have been systematic reviews on the pharmacokinetic models of isoniazid, [25][26][27] but two of these studies only provided descriptive introductions to existing articles.…”
Section: Introductionmentioning
confidence: 99%